An analytical study of biometric based remote user authentication schemes using smart cards. (April 2017) - Limbasiya, Trupil; Doshi, Nishant
Highlights: Discussed findings of the different remote user authentication systems which are focused on three-factor, two-factor, and one-factor with different attacks those are identified till date on them. Described the scenario of various attacks that makes the authentication schemes vulnerably susceptible as well as convinced the countermeasures for the same. Taxonomy about authentication attacks based on essential parameters, impression on the users, and countermeasures to prevent attacks. Graphical abstract: Abstract: In this digital era, any two entities can exchange messages, irrespective of their physical distance, via an authentication scheme on the Internet. A biometric identity is one of the unique parameters of each human being. A smart card stores such parameters based on the characteristics of an entity. Although a smart card cannot be tamper resistant, specific attacks have been identified by researchers in the context of remote user authentication schemes. Thus, motivated, we have conducted in this paper a state-of-art survey, the first of its type, on remote user authentication schemes from their inception. We have summarized and discussed distinct attacks that are likely to occur on a remote user authentication scheme and how such an attack makes a system vulnerable. Our aim is not only to document the history of findings on remote user authentication schemes but also to familiarize researchers with the list of attacks that have been identified to date.